Citizen-oriented Local Governance: the Correlation between Subjective Well-being and Citizen Participation in the Salaspils Municipality (Latvia) Case - Jēkabsone, Inga; Sloka, Biruta (Socialiniai tyrimai, 2014)
The aim of the paper is to present a possible citizen- oriented governance model and discuss the outcomes of empirical research, which are targeted to municipalities and are based on the approbation of a subjective well-being methodology. The main findings of the study show that citizen participation in decision-making processes is crucial in order to improve the well-being in the municipality. The empirical research of the Salaspils municipality and comparisons with several other municipalities in Latvia and other countries demonstrated that the citizen-oriented local governance model provides wide opportunities for improved dialogue between the municipality and society, which in turn promotes the development of a co-responsibility approach in resolving different issues within the municipality.